The dynamics of the socio-cultural life of coastal communities - Yuliana, Yuliana (Journal of Aquaculture Science, 2021)
The most important coastal socio-cultural management is the economic management of fishermen. As an archipelagic country, most of its territory consists of oceans, Indonesian fishermen should have a prosperous level of economic life. However, there are still many fishermen who are classified as poor. To improve the socio-cultural elements of the fishing community in Indonesia, a high entrepreneurial ethos is needed. This relates to the management of marine fisheries business. Aspects of short and long term planning must be prepared in detail. Sustainable development is needed to foster better utilization of marine resources. Social conditions are also related to the activities of fishermen in a social organization. Cultural conditions are the use of methods and technologies that have been used for generations to catch fish. Marine aquaculture innovation, providing freedom in a responsible manner, and respecting the rights of everyone can be done to improve the welfare and socio-cultural management of the coast. Socio-cultural transformation will give direction to economic transformation. The effort needed is to increase the knowledge of fishermen. The surrounding companies should provide business opportunities for local communities. Government policies will determine the success of coastal socio-cultural management.Keywords: management, coastal, socio-cultural